Navigating Hardships: A Mixed Method Approach of Academic Resilience amid Catastrophes among First Generation Learners of Kashmir - Ganie, Altaf Hussain; Malla, Hilal Ahmad; Ganai, Mohammad Yousuf; Omiya, Omiya (Journal of Education Method and Learning Strategy, 2025)
This study was intended to examine the impact of catastrophes among first generation learners of Kashmir and consequently how they responded the adversities. The study employed the descriptive and explanatory design. In the descriptive survey method 300 first generation learners were used as sample by means of purposive sampling with 150 male and 150 female pupils. The academic resilience was measured by means of Academic Resilience scale by Mihir Kr. Mallick and Simranjit Kaur (2017). The statistical techniques employed to measure the academic resilience are Percentage and t-Test. The results revealed that that out of 300 first generation learners of Kashmir 12, 75, 151, 38, 9, 9, and 6 have extremely high, high, above average, average, below average, low and extremely low academic resilience respectively i.e. 4%, 25%, 50.33%, 12.67%, 3%, 3% and 2%. Besides a significant difference was observed between male and female first generation learners of Kashmir, males were found to be more resilient than females. The in-depth analysis by means of interview suggested that most of the first generation learners of Kashmir are having sound academic resilience and they manage successfully the adversities like covid-19 lockdown by means of their personal positive efficacy beliefs and strong social cohesion.